DEVELOPMENT OF A POCKET BOOK ON EDUCATIONAL TOOLS FOR TEACHERS OF RAUDHATUL ANFHAL IN NORTH JAKARTA - Subur Sutrismi (International Journal of Teaching and Learning, 2025)
This study aims to develop an Educational Play Equipment Pocket Book for Raudhatul Athfal (RA) teachers in North Jakarta as a practical guide in selecting, designing, and implementing Educational Play Equipment (APE) in early childhood learning. This research follows the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted at Raudhatul Athfal (RA) in North Jakarta, involving 23 RA teachers as the research sample. Data were collected through interviews, observations, expert validation tests, and field practicality tests. The findings indicate that teachers still face limitations in utilizing APE due to the lack of systematic references. Expert validation from early childhood education specialists, instructional media experts, and curriculum experts confirmed that the pocket book is feasible for use, with an average score of 77% (Good category). Implementation across 23 RAs showed that the pocket book is practical for use, with an average practicality score of 73.62%. This pocket book helps teachers optimize the use of APE, enhances creative teaching strategies, and increases children's engagement in play-based learning activities. The study implies that the Educational Play Equipment Pocket Book can serve as an effective reference for improving teachers’ competence in APE utilization. It is recommended that this pocket book be further developed into an interactive digital format and tested on a broader scale to enhance its effectiveness in early childhood education.